Tytuły jako skrzydlate słowa - Tyrpa, Anna (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2020)
The article discusses the issue of the “second life” of titles which, separated from the original text, start to function in the texts of other authors as winged words. The author has described the works that have been written on this topic based on the materials from magazines, belles-lettres and books discussing the titles of films. Twelve titles were presented which have been taken over by the authors of at least two new texts. The research material included ten Polish novels from the years 1969-2013. Twelve titles come from two poetic works, one song, five novels and two filmed stories, one light opera and one film. Six of them are the works of Polish authors, and the remaining six were made by foreign authors. A half of them were described in the volume Skrzydlate słowa [Winged Words] of 1990.